PEMBANGUNAN APLIKASI KEAMANAN PESAN CHATTING DENGAN MENERAPKAN ALGORITMA TINY ENCRYPTION ALGORITHM (TEA) BERBASIS CLIENT SERVER - Tasya Asprina; Muh. Yamin; Sutardi Sutardi (Informatics Engineering Department of Halu Oleo University, 2018)
The development of information technology now allows one to exchange information through a computer network. One that is used in exchanging information is a chat application. The chat application is used to chat two people or more in realtime via the internet network. In exchanging information, a data security is needed, one of the data security that is done is encryption on the message. Encryption is done to change from the original message to a message that is not easy to read (ciphertext). Then a TEA (Tiny Encryption Algorithm) algorithm is applied.The results obtained in this study that the TEA algorithm can be implemented on chat messages for encryption and decryption of text messages. The process of testing encryption and decryption on messages is fast. Can be seen from the test table the application that encrypts text messages of various sizes using the same key produces a difference in the encryption and decryption time is not too large, with only a few seconds difference.Keywords—Chatting, Cryptography, TEA, Encryption, DecryptionDOI: 10.5281/zenodo.1468233